A Theoretical Study of Ordinary Dislocations and Order Twinning in γ-TiAl at Finite Temperatures - Yufeng Wen; Chengchen Jin; Yanlin Yu; Xianshi Zeng; Zhangli Lai; Kai Xiong; Lili Liu (Metals)
The generalized planar fault energies of 1/2<110] and 1/6<112] slip directions on {111} planes in <semantics>γ</semantics>-TiAl at temperatures up to 1500 K were predicted through first-principles calculations and quasi-harmonic approximation. The obtained unstable stacking and twinning fault (USF and UTF) energies, as well as superlattice intrinsic and extrinsic stacking fault (SISF and SESF) energies, are consistent with existing theoretical data. Results show that the USF, UTF, SISF, and SESF energies for both slip directions decrease overall as temperature increases. The effect of temperature on the 1/2<110] ordinary dislocation and 1/6<112] order twinning in <semantics>γ</semantics>-TiAl is further analyzed generalized planar fault energies. It is demonstrated that the nucleation of ordinary dislocation and twinning dislocations becomes more favorable with increasing temperature. Furthermore, it is shown that order twinning in <semantics>γ</semantics>-TiAl is more likely to occur at crack tips or grain boundaries, and its twinnability is enhanced at elevated temperatures.